Development and significance of antibodies to salmon calcitonin in patients with Paget's disease on long-term treatment. Issue 6092 (8th October 1977) - Woodhouse, N J; Mohamedally, S M; Saed-Nejad, F; Martin, T J
Abstract : Sixteen consecutive patients in one unit were studied during long-term treatment of Paget's disease of bone with salmon calcitonin. Eleven patients developed detectable antibody titres at some time during treatment. In one patient with a high antibody titre evidence of resistance to treatment emerged two years after the development of antibodies, but no other patient showed evidence of resistance. The clinical and biochemical response could be maintained in the absence of an acute calcium-lowering effect of calcitonin. Although antibodies often develop during treatment with heterologous calcitonin, they are only rarely the cause of clinical resistance.